On mechanical response of aluminum alloys in corrosive environment - Kumar, Sunil S; Londe, Neelakantha V; Kumar, Dilip K; Kittur, Md Ibrahim; Badruddin, Irfan Anjum; Faheem, Mohammed; Khan, Sher Afghan (Penerbit UTHM, 2022)
Al6061T6 and Al7075T6 aluminum alloys are subjected to accelerated salt spray corrosion to evaluate the amount of degradation and the effect on mechanical behavior. The specimens were stored in a closed chamber with continuous salt spray for a period of 250 hours and 500 hours, respectively. It was observed that the oxide layer was unprotective after prolonged salt spray resulting in pitting continued with exfoliation corrosion. The tensile test results show that there was a remarkable decrease in tensile properties with exposure time. A significant reduction in tensile strength, yield strength, elongation at yield, elongation at break, and overall toughness in both the alloys was observed at 500 hours. The impact strength decreased by 14.4 % and 26.47 %, Rockwell hardness (HRB) reduced by 12.2% and 20.71% for respective alloys at 500 hours of exposure. However, there was an increasing trend in elastic stiffness which attributed to a decrease in ductility. Furthermore, it was comparatively observed that Al7075T6 is more susceptible to corrosion than Al6061T6.